The application of the algorithm of the individualization of students’ physical education process - L.N. Barybina; N.A. Kolomiec; V.A. Komotskaja (Physical Education of Students, 2014)
Purpose: theoretically and experimentally justify the use of the algorithm of physical education process individualization in universities taking into account the psychophysiological features of students. Material: the study involved 413 students. It was defined indicators of the level of physical fitness and functional status, psycho-physiological features. Results: it was worked out the algorithm of individualization of students’ physical education process. It was defined the structure of the complex preparedness and it was developed models of characteristics of students - representatives of different sports specializations. It was established that for the successful construction of the training process, it is necessary to combine the parameters of physical, functional training and physiological indicators into a single integral evaluation of the individual characteristics of students. It was shown that at the students of the experimental group was improved indicators of functional, psychophysiological capabilities and physical preparedness. Conclusions: the application of the algorithm of the individualization of process of physical education enhances the functionality of the students.